Analisis Kemampuan Berpikir Kritis Peserta Didik Melalui Implementasi Pembelajaran Online - Sonya Sonya; Ibrahim Ibrahim; Fatmawati Fatmawati (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2022)
This study aimed to determine the critical thinking skills of students at MTs Negeri Tarakan through the implementation of online learning. This pre-experimental research used one shot case study design. The research subjects were students of class VIII C of MTs Negeri Tarakan, where sample was determined using a purposive sampling technique. The data was obtained from the results of critical thinking ability test in the form of description questions. The results of the one sample t-test showed that the t-count = -17.106 with dk= 34 and the t-table = 1.691. As the t-count t-table, the Ho was accepted, meaning that the average value of students’ critical thinking skills was lower than 70. The percentage of achievement of each indicator or critical thingking ability were 52% for providing a simple explanation (modearate category), 39% for concluding indicators (low category), 56% for providing further explanation (moderate category), and 71% for setting strategies and tactics (high category). The average achievement of critical thingking ability indicators was 54% (moderate category). Thus, it was necessary to train students’ critical thingking skills through the learning process by using the right model and applying critical thinking indicators. Keywords: Critical Thinking Ability, Online Learning, Indicator